Local Rigidity by Flexibility: Unusual Design for Organic THz-Device Materials - Kim, Dong Joo; Yu, In Cheol; Jazbinsek, Mojca; Kim, Chaeyoon; Yoon, Woojin; Yun, Hoseop; Kim, Sang Wook; Kim, Dongwook; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2023)
Terahertz (THz) waves interact with molecular phonon vibrations of organic matter. When designing organic THz-device materials, conformational flexible groups (CFGs) are in most cases avoided. CFGs create many low-energy conformers with high conformational entropy, which results in large and many phonon vibration modes that lead to undesired self-absorption of THz waves. Here, nonpolar CFGs only having weak intermolecular interaction capability are unusually introduced into organic THz-device materials, utilized for efficient THz wave generation. Newly designed THz-source crystals possess nonpolar methylene -(CH2)n- units having high conformational flexibility. Compared to previously reported benchmark crystals without methylene CFGs, introducing methylene CFGs significantly reduces void volume in newly designed crystals. This leads to the suppression of molecular phonon vibrations below 2.0 THz (i.e., introducing flexibility results in local rigidity). At infrared pump wavelengths, new CFG-contained crystals generate a strong THz electric field that is one order of magnitude stronger than that generated in inorganic ZnTe crystals. CFG-contained crystals exhibit a flatter spectral shape of the generated THz wave than benchmark crystals without methylene CFGs. Therefore, the introduction of CFGs is a very intriguing design strategy for organic THz-device materials to reduce the limitations caused by phonon vibrations.
Keywords: Device materials; Energy conformers; Lower energies; Molecular phonons; Non-polar; Organic crystal; Organics; Phonon vibrations; Tera Hertz; Terahertz device; nonlinear optics; organic crystals; terahertz waves